The impact of design in mobile surveys: relationships between light modes, number of questions and response time - Trombeta Santos, Gabriela (InfoDesign, 2022)
This study assessed whether the design of screens in light mode (white background with dark text) or dark mode (dark background with light text) impacts the number of questions and time that people answer mobile surveys. The study relied on human-centered design processes (observation, generation, prototyping and testing). Twenty adults took part in usability tests and 120 received a link to answer a long survey on their cell phones, and clicked on "give up" when they got tired. Though most participants reported a preference for dark mode, and the mean number of dark mode responses was higher, statistical tests did not indicate significant differences between groups. This data suggests that the use of light or dark designs did not sufficiently influence the number of questions that participants answered and the time they took to do that.